Regulation of Preferential Flow by Soil Thickness on Small Hillslopes With Complex Topography Through Intensive High‐Frequency Soil Moisture Monitoring - Jun Zhang; Sheng Wang; Zhiyong Fu; Fa Wang; Kelin Wang; Hongsong Chen (Geophysical Research Letters)
Abstract Preferential flow (PF) is a relatively rapid water movement that significantly impacts geophysical processes. However, identifying PF and its environmental control mechanisms remains challenging, primarily due to soil spatial heterogeneity. In this study, 20 sensors were installed on two hillslopes with distinct soil thicknesses to monitor moisture at 5‐min intervals. PF types were identified based on moisture response sequence to rainfall across layers, and relationships among PF frequency (PFF), soil depth, and rainfall characteristics were determined. Macropore flow was the main PF type, followed by soil‒bedrock interface flow. On the hillslope with deep soil cover, PFF was significantly negatively correlated with soil depth. Comparison, on the hillslope with shallow soil cover, PFF was not influenced by soil depth but more notably controlled by rainfall intensity and antecedent soil moisture. Accordingly, these findings highlight the critical roles of the soil thickness in shaping PF characteristics.